Cryptosporidium spp. in Argentina: epidemiology and research advances in human, animal, and environmental settings during the 21st century - Rivero, Maria Romina; Vissio, Claudina; Feliziani, Constanza; De Angelo, Carlos; Touz, Maria Carolina; Tiranti, Karina; Lombardelli, Joaquín Andrés; Duartez, Florencia Judith; Curletto, Lumila (Frontiers in Microbiology, 2025)
IntroductionCryptosporidium spp. is an intestinal protozoan causing cryptosporidiosis, a diarrheal disease affecting humans and animals, with zoonotic potential. In immunocompromised individuals, infections can be severe or fatal. It is a major waterborne parasite and a leading cause of neonatal diarrhea in calves. This study systematically reviews Cryptosporidium spp. research in Argentina during the 21st century, highlighting its epidemiological significance and research gaps.MethodsA systematic review following PRISMA guidelines was conducted using LILACS, PubMed, Scopus, and SciELO Argentina. Eligible studies (2001–2024) included human (community and hospital-based), animal (domestic, wild, and captive), and environmental (water, soil and vegetable) surveys. The review analyzed epidemiology, diagnosis, treatment, genetic diversity, distribution, and risk factors.ResultsOf 277 articles reviewed, 66 met eligibility criteria. Cryptosporidium spp. was detected in 17 of Argentina’s 23 provinces, mainly in the Pampean region. Five species were identified (C. hominis, C. parvum, C. suis, C. scrofarum, and C. varanii), though genetic diversity studies remain limited. Human cryptosporidiosis primarily affects immunocompromised individuals (HIV/AIDS, transplant recipients, hematologic cancer patients). The parasite was found in feces, duodenal biopsies, blood, sputum, and cerebrospinal fluid, with complications such as cholangiopathy and pulmonary cryptosporidiosis. Infections with C. hominis and C. parvum (including co-infections) were observed, with multiple subtypes documented. In animals, C. parvum was prevalent in Pampean calves, while C. suis and C. scrofarum were found in domestic pigs. Wildlife, including non-human primates and coypu, also tested positive. Cryptosporidium was detected in recreational and drinking water samples. No Cryptosporidium spp. oocysts were detected in soil. Risk factors included socio-economic conditions and animal management practices.ConclusionCryptosporidium spp. is widely distributed in Argentina, yet eco-epidemiological transmission factors remain poorly understood, hindering control strategies. Limited research on genetic diversity and distribution highlights the need for further studies, particularly in vulnerable populations and areas of close human-animal interaction, such as productive systems. The presence of Cryptosporidium spp. in water underscores the importance of improving public health policies and water treatment standards. From a One Health perspective, these findings emphasize the need for enhanced epidemiological surveillance and research to strengthen prevention and control in Argentina.